A boilerplate that can reduce software ambiguity in Chinese software requirements - Osman, Mohd Hafeez; He, Jiaying; Ng, Keng Yap; Hassan, Sa'adah (Little Lion Scientific R&D, 2024)
During the rapid process of software development, requirements engineering plays a crucial role in ensuring the success of software projects. Clear and accurate requirements specification directly impact the effectiveness of project implementation, influences customer satisfaction, and ultimately determines the overall success rate of the project. However, ambiguity and structural issues are common in Chinese software requirements, which can hinder understanding and implementation. These issues not only increase the complexity of project execution but may also lead to extended development cycles and wasted resources. To address these challenges, this paper aims to develop a set of Chinese-based software requirement boilerplate to improve the clarity and accuracy of requirements specification. The boilerplate is designed with consideration for Chinese grammar conventions and international standards, offering a universal and user-friendly solution. This paper reviews related literature, discuss the limitations of current requirements specification method, and details the boilerplate design process and evaluation methodology. The effectiveness of the boilerplate is demonstrated through the reconstruction of requirements statements across various software industries, complemented by expert assessments and feedback from industry professionals. This study provides a practical foundation for Chinese software requirements specification, aiming to enhance the quality and efficiency of requirements expression.